Sex-differences in the multidimensional evaluation of dyspnea in respiratory outpatients - Milne, Kathryn M.; Zhang, Julia; Harris, Owen D.; Guenette, Jordan A. (Frontiers in Medicine, 2025)
BackgroundFemales experience greater dyspnea intensity compared to males. The role of sex in dyspnea quality and emotional responses in respiratory outpatients is unknown. The aim of this study was to examine sex-differences in dyspnea quality and affective distress as well as relationships between dyspnea, anxiety, and depression.Materials and methodsRespiratory outpatients rated chronic exertional dyspnea intensity and impact using the modified Medical Research Council (mMRC) dyspnea scale. Participants selected qualitative dyspnea descriptors from an established list of 15 descriptors and completed the Multidimensional Dyspnea Profile (MDP). Symptoms of anxiety and depression were assessed using the Hospital Anxiety and Depression Scale (HADS).ResultsParticipants (n = 78) had a variety of common respiratory diagnoses. Males and females experienced similar dyspnea impact (mMRC) and were matched for relative impairment in lung function. Females rated higher intensity of breathing muscle work, chest tightness, and mental effort. The affective response to dyspnea was greater in females, with significantly higher reports of anxiety, frustration, and fear related to dyspnea. HADS anxiety subscale scores were correlated with MDP dyspnea scores of breathing discomfort, immediate perception domain, and emotional response domain in males. In females, higher HADS anxiety scores were correlated with the emotional response domain only. Males with higher likelihood of anxiety experienced greater frustration, anger, and fear related to dyspnea; however, this was not the case for females.ConclusionIn respiratory outpatients, despite similar lung function impairment and mMRC scores, females experience greater breathing muscle work, chest tightness, and mental effort as well as significantly greater anxiety, frustration, and fear related to dyspnea.